Kajian Manfaat Alkitab Menurut 2 Timotius 3:16 Dan Implikasinya Bagi Orang Percaya Masa Kini - Marthen Mau (Manna Rafflesia, 2021)
The only special revelation is the Bible which God has breathed as the main source for human learning, so that it can organize his life responsibly in service and life every day. Today some people think that the Bible is outdated and of no longer useful to mankind because this is the age of science, technology, and art. However, some people still believe that the Bible is very useful for mankind, therefore the Bible must be studied carefully so that the contents of the Bible are understood as a whole. This paper aims to encourage and inspire new enthusiasm for believers to be active in studying God's word that has been breathed by God because reading God's words can show that God is speaking to his readers. This paper uses a qualitative research method with a deep exegetical study approach. Therefore, this article provides a viewpoint for believers to be loyal in reading the Bible because the Bible is very useful for believers to imply in today's life.